Effect of sintering additives on the properties of alumina toughened zirconia (ATZ) - Abbas M.K.G.; Ramesh S.; Tasfy S.F.H.; Lee K.Y.S.; Gul M.; Aljaoni B. (Springer Nature, 2024)
The effect of small amounts of copper oxide, manganese oxide, and stainless steel as sintering additives on the sintering behavior and mechanical properties of Alumina Toughened Zirconia (ATZ, 3Y-TZP with 20 wt% Al2O3) ceramic composites were evaluated and contrasted with that of undoped ATZ by using microwave sintering (MW) method. Green bodies were sintered at 1250C, 1350C, and 1500C using a holding time of 5min., with a heating rate of 30C /min. In general, all ATZ samples exhibited a similar trend, as the results showed that the relative density and mechanical properties increased with increasing sintering temperature regardless of the addition of dopants. It was found that the addition of 0.2 wt% CuO, 0.5 wt% MnO2, and 0.2 wt% SS were beneficial in enhancing the densification and improving the mechanical properties of ATZ without inducing grain coarsening. The ATZ composite samples' relative density, tetragonal phase stability, microstructural evolution, Vickers hardness, and fracture toughness were revealed. The addition of 0.2 wt% CuO was the most beneficial in improving the properties of ATZ at a low sintering temperature of 1250C since the sample obtained the highest relative density of 97%, Vickers hardness of 13.2GPa and fracture toughness of 6.5MPa m1/2. In contrast, the undoped ATZ required a high sintering temperature to achieve comparable results to the doped samples. The ANOVA analysis revealed that the CuO-doped ATZ sample exhibited the highest significance and was the most suitable in improving both hardness (H) and fracture toughness (KIc) across all temperature conditions. This study also proved that the microwave sintering technique promotes the densification and mechanical properties of ceramic composites compared to the conventional sintering technique. Graphical abstract: [Figure not available: see fulltext.]. 2023, The Author(s).